Urgensi Pembuatan Sertifikat Tanah Jalan Oleh Pemerintah - Desita Winanti Putri (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2018)
Road as one of the social functions of the land controlled by the state of its arrangement is divided into of Law no. 5 of 1960 on The Basic Regulations of Agrarian Principles (UUPA) and the Road Law. As a form of proof that roads of a certain size have been controlled by the state, the government carries out the process of certifying the land of the road. The road soil certification aims to protect its social function as a means of land transportation, as provided for in the Road Law. The certification of road soil is not easily carried out, but it can lead to new problems, in the form of a dikoktomi on roads that have been certified with land that has not been certified. This dichotomy indicates that the control of land by the state is very weak -on one side- and -on the other side- it is as if the parties can easily master the social function of the land used as the road. therefore the recommendation is made that the Government is expected to make a law which regulates the land so that it is not bound to The Basic Regulations of Agrarian Principles (UUPA), due to its different functions, so it is not necessary to be certified on the road, but only with documents about the size of the road that is not in the form of a certificate of rights.